2017
DOI: 10.3389/fnins.2017.00328
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Signaling Pathway in Arcuate Feeding-Related Neurons: Role of the Acbd7

Abstract: The understanding of the mechanisms whereby energy balance is regulated is essential to the unraveling of the pathophysiology of obesity. In the last three decades, focus was put on the metabolic role played by the hypothalamic neurons expressing proopiomelanocortin (POMC) and cocaine and amphetamine regulated transcript (CART) and the neurons co-localizing agouti-related peptide (AgRP), neuropeptide Y (NPY), and gamma-aminobutyric acid (GABA). These neurons are part of the leptin-melanocortin pathway, whose r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 100 publications
1
10
0
Order By: Relevance
“…Previous work by Buniello and colleagues used the Genome Wide Association Studies catalogue for phenotypic risk association [ 38 ] and found that five DNA variants upstream of ACBD3 (three intergenic variants and two regulatory region variants) were associated with core binding factor acute myeloid leukaemia risk [ 39 ]. There was one other risk variant, but this was not linked to cancer but rather behaviour which is not unexpected given that several other ACBD family proteins are known to influence behaviour in animals [ 40 , 41 , 42 ]. The Genehancer database was also searched, corroborating that the same five ACBD3 variants were associated with core binding factor acute myeloid leukaemia risk; additionally, ACBD3 regulatory region variants were found that enhanced the red blood cell distribution width (a measure of red blood cell volume variation), and variants that are associated with plateletcrit (the percentage of blood volume occupied by platelets) [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous work by Buniello and colleagues used the Genome Wide Association Studies catalogue for phenotypic risk association [ 38 ] and found that five DNA variants upstream of ACBD3 (three intergenic variants and two regulatory region variants) were associated with core binding factor acute myeloid leukaemia risk [ 39 ]. There was one other risk variant, but this was not linked to cancer but rather behaviour which is not unexpected given that several other ACBD family proteins are known to influence behaviour in animals [ 40 , 41 , 42 ]. The Genehancer database was also searched, corroborating that the same five ACBD3 variants were associated with core binding factor acute myeloid leukaemia risk; additionally, ACBD3 regulatory region variants were found that enhanced the red blood cell distribution width (a measure of red blood cell volume variation), and variants that are associated with plateletcrit (the percentage of blood volume occupied by platelets) [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found that oral administration of PNE activated hypothalamic nuclei, both the ARC and PVN, but not the VMH. In the melanocortin system, two types of ARC neurons—the POMC and NPY/AgRP—project to MC4R-expressing PVN neurons and regulate PVN neuronal activity by releasing α-MSH and γ-aminobutyric acid (GABA), respectively [ 32 , 34 , 35 ]. Moreover, several studies have shown that modulation of POMC neuronal activity is closely related to the MC3 and MC4Rs, although POMC neurons innervate MC4R-expressing neurons in the PVN [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This results in the proteolytic conversion of POMC and the release of α-MSH, which activates MC4R, promoting satiety, reduced food intake and increased energy expenditure. Leptin also binds to AgRP neurons, resulting in the suppression of AgRP release, which is a potent antagonist for MC4R and increases food intake, energy conservation and weight [ 241 , 242 ]. An incretin hormone GLP1 (glucagon-like peptide-1) that stimulates insulin secretion, and PYY (peptide YY), both secreted from the gastrointestinal tract, are also anorexigenic and delay gastric emptying and promote satiety [ 243 ].…”
Section: Mechanisms Of Chrononutrition In Energy Homeostasis and Obesitymentioning
confidence: 99%